2021
DOI: 10.3390/jmse9101100
|View full text |Cite
|
Sign up to set email alerts
|

Design of Diamond Bits Water Passage System and Simulation of Bottom Hole Fluid Are Applied to Seafloor Drill

Abstract: The performance of the diamond bit directly affects the drilling efficiency of the seafloor drill. The drill bits used in land drilling are prone to abnormal wear, low coring efficiency, and large sample disturbance in marine exploration. At first, in this paper, the operation and formation characteristics of a seafloor drill are utilized to design a water passage system for bottom-jetting diamond bits based on the multi-objective optimization theory. Additionally, then, fluid dynamics theory and the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In order to increase the intensity of sludge removal from the bottom of wells, studies of the culvert system of the drill bit were carried out [8]. It was found that the flow field of the washing fluid at the bottom becomes more turbulent while the efficiency of removal of the bearing sludge decreases as the height of the bit penetration increases.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In order to increase the intensity of sludge removal from the bottom of wells, studies of the culvert system of the drill bit were carried out [8]. It was found that the flow field of the washing fluid at the bottom becomes more turbulent while the efficiency of removal of the bearing sludge decreases as the height of the bit penetration increases.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%